2012
DOI: 10.5812/hepatmon.6144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of HIV, Syphilis, Hepatitis B and C Among Female Prisoners in Isfahan, Iran

Abstract: BackgroundFemale prisoners are at risk of acquiring sexually transmitted infections (STIs). There has been no previous study regarding the epidemiological status of STIs among female prisoners in Isfahan, central Iran.ObjectivesThe aim of this study was to investigate the prevalence and risk factors of the aforementioned infections among women incarcerated in the central prison, Isfahan, to determine appropriate prevention measures.Patients and MethodsIn a cross-sectional study, all of the 163 women incarcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 13 publications
8
42
3
6
Order By: Relevance
“…In the context of vulnerability, investigators consider some populations as more likely to acquire syphilis: individuals living in seclusion, homeless people, drug users, men who have sex with men (MSM), those co-infected with human immunodeficiency virus (HIV), and pregnant women [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of vulnerability, investigators consider some populations as more likely to acquire syphilis: individuals living in seclusion, homeless people, drug users, men who have sex with men (MSM), those co-infected with human immunodeficiency virus (HIV), and pregnant women [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…the trend shown in the survey is that over the years the prevalence of HIV/AIDS increased, even with the applied interventions [18].…”
Section: Thematic Axis 3 Facing Hiv/aids Interventionsmentioning
confidence: 98%
“…During the years investigated there was variation in the prevalence of cases HIV/ AIDS, the largest evidenced in 2005, where there were studied 4920 prisoners and the result was of 4.86% (239) positive cases and the lowest was in 1997 with 2022 inmates examined presenting the result was positive for 0.15% (03) [18].…”
Section: Thematic Axis 3 Facing Hiv/aids Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exposure to maternal blood can also occur with CS; accordingly, there is no reason to offer elective caesarean section to HCV-infected parturients [11][12][13][14] , with respect to special circumstances when CS is preferred to NVD, such as membranous rupture and internal fetal monitoring are confirmed to be associated with HCV transmission. CS and its complications were the main cause of death in many developing countries [15][16][17][18] . Egypt has the highest HCV prevalence worldwide; therefore, our results showed that the prevalence of HCV in a sample of Egyptian pregnant women was 2.08% (80 of 3,836 women), based on HCV Ab and PCR testing.…”
Section: Discussionmentioning
confidence: 99%